Medical student's attitudes toward obstetrics and gynecology clerkship at the Far Eastern University Nicanor Reyes Medical Foundation Medical Center. - Cruz, Jessica Ona
Purpose of the study: The aim of this study is to determine whether there will be changes in the attitudes of medical students towards the Obstetrics and Gynecology rotation at the Far Eastern University Nicanor Reyes Medical Foundation Medical Center. It also aims to explore the reasons behind these changes. These attitudes are toward three aspects of the rotation namely, the teaching-learning activities, the staff and the specialty field as a career option. Methodology: Sixty students (fourth year junior interns or medical clerks) rotating in the Department of Obstetrics and Gynecology of the Far Eastern University Nicanor Reyes Medical Foundation Medical Center were given pre-rotational questionnaires concerning their attitudes towards the teaching-learning tasks (including the duties and responsibilities while rotating in the department), towards the consultants, residents and staff nurses, and towards Obstetrics and Gynecology as a future career choice. The questionnaires were in the form of semantic differential scales and ranking. The same set was given on the last days of rotation. The before- and after-rotation responses were compared using the Wilcoxon Index. Focus group discussions were carried out to explore the reasons and explanation behind responses. As indirect indicators for attitude change, mean entry test and history scores were also compared to mean exit scores using the T-test. Results showed that activities that were initially viewed as favorable received even more favorable results after rotation while those activities scored unfavorably got more unfavorable responses. Favored tasks included conferences, ward rounds, outpatient activities and surgical procedures. In these activities, students felt more actively involved, they perceived their roles were more significant as part of the team, there were less occasions for reprimand (friendlier), and they felt that the outcome of accomplishing the task compensated the effort they have invested on it. Staff members also received favorable responses before and after rotation in all the scales. As a career option, seventy percent of respondents included the field as an option before rotation. At the end of rotation, there were three who dropped OB-GYN as one of their choices but three students included it such that at end rotation, the field retained its previous ranking. The general trend of favorable responses were supported by significantly higher mean test scores on the exit exams and histories. Conclusions: Results of the study illustrate that elements of the rotation served to reinforce and strengthen pre-rotational attitudes that students held at the start. The fact that favorable views were held for most of the activities suggests that the clerkship training provided or satisfied major motivational factors and learning conditions that are important for the acquisition of knowledge, skills and attitudes in the specialty field. However, the persistence of unfavorable views to a few equally essential activities also suggests that training in these areas must be modified to accommodate important motivational and learning needs of the medical clerks. Through these modifications, negative views can be reduced and positive ones introduced as these do much to optimize student learning.